2015
DOI: 10.4321/s1578-84232015000300007
|View full text |Cite
|
Sign up to set email alerts
|

Niveles de ira en practicantes de boxeo y kickboxing: diferencias en función de la disciplina y el nivel deportivo

Abstract: Niveles de ira en practicantes de boxeo y kickboxing: diferencias en función de la disciplina y el nivel deportivo Anger intensity in boxing and kickboxing practitioners: differences based on discipline and competitive level Niveis do ira na prática e kickboxing boxe: diferenças em termos de disciplina e nível esportivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
1
1
Order By: Relevance
“…In particular, the results showed that the high anger profile was the most represented in terms of professional players whereas the low anger profile was overrepresented among amateur players. The significant difference identified in the present study between professional versus amateur players contradicts the results of previous studies in other sports which showed that amateur players reported significantly higher levels of anger Menéndez-Santurio & Fernández-Río, 2015). As this is the first study, to our knowledge, to report that amateur players reported lower symptoms of anger in comparison to professional players, future research should test this relationship again to see whether it emerges in other samples, or whether it was a result specific to the current sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, the results showed that the high anger profile was the most represented in terms of professional players whereas the low anger profile was overrepresented among amateur players. The significant difference identified in the present study between professional versus amateur players contradicts the results of previous studies in other sports which showed that amateur players reported significantly higher levels of anger Menéndez-Santurio & Fernández-Río, 2015). As this is the first study, to our knowledge, to report that amateur players reported lower symptoms of anger in comparison to professional players, future research should test this relationship again to see whether it emerges in other samples, or whether it was a result specific to the current sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Martinent and collaborators (Martinent & Ferrand, 2009;Martinent et al, 2012) found that anger and anxiety were the most difficult emotions to handle in table tennis players. Moreover, some studies showed that high anger levels were experienced by amateur table-tennis players but not professional and international ones Menéndez-Santurio & Fernández-Río, 2015).…”
Section: Perceived Anger Profiles In Table Tennis Players: Relationsh...mentioning
confidence: 99%
“…As previous studies showed, anger control is necessary to perform in table tennis because this surplus energy can lead to poor sport performance (Martinent et al, 2013;Steffgen, 2017). Table tennis players who compete in greater leagues express their external anger less than those who compete in lower leagues due to the greater control that anger requires (Menéndez-Santurio & Fernández-Río, 2015). Even, these outcomes could be determined by the application of rules, because of the rules are taken less seriously in lower competition levels, whereas in higher leagues or competitions a bad behaviour could lead to an admonishment.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there is a relationship between anger and sport performance (Davis, 2011;Davis et al, 2010;Martinent et al, 2011). And Thirdly, several studies have shown differences in anger levels in other sports depending on competition level (González-García, 2017; Hanin, 2007;Hanton et al, 2000;Menéndez-Santurio & Fernández-Río, 2015). Therefore, the aim of this study was to determine if there are differences in anger levels depending on sport performance level in table tennis players.…”
Section: Introductionmentioning
confidence: 94%
“…Los resultados mostraron que no existe covariación en función de los éxitos deportivos (locales, regionales, nacionales e internacionales) en los niveles de apoyo familiar e ira. Estos resultados, contradicen las hipótesis establecidas en el inicio del trabajo en base a estudios anteriores, en los que la ira es una variable que si se ve mediada por el nivel de éxitos de los deportistas (Davis, 2011;Davis et al, 2010;Menéndez-Santurio y Fernández-Río, 2015;Wittmann et al, 2008). Por lo tanto, no se encontró que esta variable mostrara covariación con el apoyo familiar y los niveles de ira.…”
Section: Discusión Y Conclusionesunclassified